Effect of Social Suport and Social Interaction on Anxiety Among Pregnant Women - Simarmata, Imelda Dearni; Budihastuti, Uki Retno; Tamtomo, Didik (Journal of Maternal and Child Health, 2019)
Background: There is growing evidence that the antenatal period is a time of increased liability to mental disorders. The most common psychiatric illnesses during pregnancy and the postpartum period are depressive and anxiety disorder. The purpose of this study was to examine the effect of social support and social interaction on anxiety among pregnant women. Subjects and Method: A cross-sectional study was carried out in community health centers in Kutai Kartanegara, East Kalimantan, from November to December 2018. A sample of 200 pregnant women was selected by simple random sampling. The dependent variable was anxiety. The independent variables were education, parity, stress, family income, family support, social interaction, and counseling. The data were collected by questionnaire and analyzed by multiple linear regression. Results: Anxiety among pregnant women increased with stress (b= 0.33; 95% CI= 0.16 to 0.49; p= 0.001). It was decreased by high education (b= - 2.37; 95% CI= -3.93 to -0.81; p= 0.003), high income (b= -4.69; 95% CI= -7.81 to -1.57; p= 0.003), parity (b= 0.38; 95% CI= -2.98 to -0.26; p= 0.001), strong family support (b= -0.38; 95% CI= 0.52 to 0.24; p= 0.001), social interaction (b= -0.27; 95% CI= -0.42 to -0.12; p= 0.001), and conselling (b= -0.91; 95% CI= - 1.77 to -0.05; p= 0.004). Conclusion: Anxiety among pregnant women increases with stress. It is decreased by high education, high income, parity, strong family support, social interaction, and counseling. Keywords: anxiety, stress, social interaction, pregnant women Correspondence: